Glaucoma-related Changes in the Mechanical Properties and Collagen Micro-architecture of the Human Sclera. - Baptiste Coudrillier; Jacek K Pijanka; Joan L Jefferys; Adhiraj Goel; Harry A Quigley; Craig Boote; Thao D Nguyen (PLoS ONE)
Objective The biomechanical behavior of the sclera determines the level of mechanical insult from intraocular pressure to the axons and tissues of the optic nerve head, as is of interest in glaucoma. In this study, we measure the collagen fiber structure and the strain response, and estimate the material properties of glaucomatous and normal human donor scleras. Methods Twenty-two posterior scleras from normal and diagnosed glaucoma donors were obtained from an eyebank. Optic nerve cross-sections were graded to determine the presence of axon loss. The specimens were subjected to pressure-controlled inflation testing. Full-field displacement maps were measured by digital image correlation (DIC) and spatially differentiated to compute surface strains. Maps of the collagen fiber structure across the posterior sclera of each inflated specimen were obtained using synchrotron wide-angle X-ray scattering (WAXS). Finite element (FE) models of the posterior scleras, incorporating a specimen-specific representation of the collagen structure, were constructed from the DIC-measured geometry. An inverse finite element analysis was developed to estimate the stiffness of the collagen fiber and inter-fiber matrix. Results The differences between glaucoma and non-glaucoma eyes were small in magnitude. Sectorial variations of degree of fiber alignment and peripapillary scleral strain significantly differed between normal and diagnosed glaucoma specimens. Meridional strains were on average larger in diagnosed glaucoma eyes compared with normal specimens. Non-glaucoma specimens had on average the lowest matrix and fiber stiffness, followed by undamaged glaucoma eyes, and damaged glaucoma eyes but the differences in stiffness were not significant. Conclusion The observed biomechanical and microstructural changes could be the result of tissue remodeling occuring in glaucoma and are likely to alter the mechanical environment of the optic nerve head and contribute to axonal damage.